Peacebuilding in the African Union : law, philosophy and practice - Jeng, Abou. (Cambridge : Cambridge University Press, 2012)
"Particularly in the context of internal conflicts, international law is frequently unable to create and sustain frameworks for peace in Africa. In Peacebuilding in the African Union, Abou Jeng explores the factors which have prevented such steps forward in the interaction between the international legal order and postcolonial Africa. In the first work of its kind, Jeng considers whether these limitations necessitate recasting the existing conceptual structure and whether the Constitutive Act of the African Union provides exactly this opportunity through its integrated peace and security framework. Through the case studies of Burundi and Somalia, Jeng examines the structures and philosophy of the African Union and assesses the capacity of its practices in peacemaking. In so doing, this book will be of great practical value to scholars and legal practitioners alike"--
Machine generated contents note: 1. Introduction; 2. International law and postcolonial Africa; 3. Violence and conflicts in Africa; 4. Institutional responses to conflicts; 5. Genesis of the African Union; 6. Structures and philosophy of the African Union; 7. The African Union's peacebuilding travails in Burundi; 8. The African Union and peace initiatives in post-state Somalia; 9. Towards an African Union philosophy on peacebuilding?.
Includes bibliographical references and index.
Keywords: African Union; Peace-building -- Africa; POLITICAL SCIENCE / Political Freedom & Security / Human Rights